The mediation process : practical strategies for resolving conflict - Moore, Christopher W. (2014)
"This is the fourth edition of one of the seminal works in the field of mediation and conflict resolution. The book is practical blend of theory, research, and practice with a useful "how to" approach to resolving disputes at various stages of development and resolution. Its case studies present a range of successful applications of mediation (interpersonal, child custody and divorce, commercial, business, organizational, public policy, environmental, intercultural and international) and strategies for intervention. The book is written for both beginning and experienced practitioners. "--
Keywords: Mediation; Ethnic conflict; Conflict management; LAW / Alternative Dispute Resolution